Validity, Agreement and Reliability of the ForceFrame Dynamometer in Patients with Anterior Cruciate Ligament Injury - Kamilla Arp; Thomas Frydendal; Troels Kjeldsen; Ulrik Dalgas; Signe Timm; Bjarke Viberg; Kim Ingwersen; Claus Varnum (International Journal of Sports Physical Therapy)
# Background